1976
DOI: 10.1037/0033-2909.83.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

White preference in Blacks: A paradigm in search of a phenomenon.

Abstract: Most reviews of the research on preference behavior in blacks, including that of Brand, Ruiz, and Padilla, have criticized that body of literature primarily with regard to problems of internal and external validity. However, it is the contention here that a more essential weakness has existed in the investigations of preference behavior in blacks, namely, the failure of researchers to evoke in that population choice responses that depart from chance. A review of the most prominent studies reveals that the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 34 publications
2
77
0
Order By: Relevance
“…In response to these fi ndings and subsequent research, Williams, Best, and Boswell (1975) suggested evolutionary principles to explain this apparent White bias in both White and African American children. It is important to note that subsequent analyses suggested that Black children did not favor White over Black dolls, but merely favored Black dolls less strongly than White children favored White dolls (Banks, 1976 ). The same pattern of fi ndings, in which children who are in the racial majority have stronger ethnocentrism than minority children, has been detected for children outside of the United States.…”
Section: Evolutionary P Erspectivessupporting
confidence: 51%
“…In response to these fi ndings and subsequent research, Williams, Best, and Boswell (1975) suggested evolutionary principles to explain this apparent White bias in both White and African American children. It is important to note that subsequent analyses suggested that Black children did not favor White over Black dolls, but merely favored Black dolls less strongly than White children favored White dolls (Banks, 1976 ). The same pattern of fi ndings, in which children who are in the racial majority have stronger ethnocentrism than minority children, has been detected for children outside of the United States.…”
Section: Evolutionary P Erspectivessupporting
confidence: 51%
“…In particular, concerns have been raised about the internal and external validity of previous research, mostly related to demand characteristics and experimenter bias (Banks, 1976;Rosenberg, 1989). The present study reexamined the issue of young children's skin tone preferences by testing both Black and White preschool children and taking precautions to control for demand characteristics and experimenter bias.…”
Section: Discussionmentioning
confidence: 99%
“…These youngsters may be alienated from mainstream society, feeling prejudice and discrimination, and frustration about the lack of positive future prospects. The constant danger of becoming involved in social violence has the end result of low self-esteem (Banks 1976). Table 3 shows that their mothers worry very much about potential discrimination against their children.…”
Section: S-w Kangmentioning
confidence: 99%